The Influence of Facilities and Accessibility on Visitor Satisfaction of Sekumpul Waterfall - I Made Deva Surya Wiryawan; Ni Nyoman Yulianthini (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
This study aims to analyze the influence of facilities and accessibility on the satisfaction of visitors to Sekumpul Waterfall. The main problem in this study is that the quality of facilities and access to tourist sites is not optimal which has the potential to affect the level of visitor satisfaction. This study uses a quantitative approach with data collection techniques through a Likert scale questionnaiThis study aims to analyze the influence of facilities and accessibility on the satisfaction of visitors to Sekumpul Waterfall. The main problem in this study is that the quality of facilities and access to tourist sites is not optimal which has the potential to affect the level of visitor satisfaction. This study uses a quantitative approach with data collection techniques through a Likert scale questionnaire that has been tested for validity and reliability. The population in this study is all domestic visitors who have visited Sekumpul Waterfall and the number of samples used in this study is 110 respondents. The data were analyzed using classical assumption tests and multiple linear regression. The results of the study show that (1) facilities and accessibility simultaneously have a positive and significant effect on visitor satisfaction. (2) Facilities have a positive and significant effect on visitor satisfaction. (3) Accessibility has a positive and significant effect on visitor satisfaction. Thus, improving the quality of facilities and accessibility in an integrated manner is essential to increase visitor satisfactionre that has been tested for validity and reliability. The population in this study is all domestic visitors who have visited Sekumpul Waterfall and the number of samples used in this study is 110 respondents. The data were analyzed using classical assumption tests and multiple linear regression. The results of the study show that (1) facilities and accessibility simultaneously have a positive and significant effect on visitor satisfaction. (2) Facilities have a positive and significant effect on visitor satisfaction. (3) Accessibility has a positive and significant effect on visitor satisfaction. Thus, improving the quality of facilities and accessibility in an integrated manner is essential to increase visitor satisfaction